1997
DOI: 10.2307/3433246
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated Body Burden and Endogenous Release of Lead in Employees of a Lead Smelter

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 14 publications
5
38
0
2
Order By: Relevance
“…Chelatable lead was found to correlate with lead in biopsies of the vertebrae (a mosdy trabecular bone), but not KXRF-measured lead in finger bone (which is mostly cortical bone) (65). Fleming et al (66) on the other hand, found that the relationship of KX.RFmeasured bone lead to blood among lead smelter workers who had not worked for 10 months, as well as retired lead smelter workers, was stronger for the tibia (cortical bone) than the calcaneus (trabecular bone). One potential explanation is that although bone mineral density of the calcaneus has been reported to be a good indicator of overall trabecular bone density (62'), the error for calcaneal measurements is generally larger than that of tibia measurements, which may have resulted in a more attentuated bone lead-blood lead relationship.…”
Section: Conceptual Paradigmsmentioning
confidence: 99%
“…Chelatable lead was found to correlate with lead in biopsies of the vertebrae (a mosdy trabecular bone), but not KXRF-measured lead in finger bone (which is mostly cortical bone) (65). Fleming et al (66) on the other hand, found that the relationship of KX.RFmeasured bone lead to blood among lead smelter workers who had not worked for 10 months, as well as retired lead smelter workers, was stronger for the tibia (cortical bone) than the calcaneus (trabecular bone). One potential explanation is that although bone mineral density of the calcaneus has been reported to be a good indicator of overall trabecular bone density (62'), the error for calcaneal measurements is generally larger than that of tibia measurements, which may have resulted in a more attentuated bone lead-blood lead relationship.…”
Section: Conceptual Paradigmsmentioning
confidence: 99%
“…Chelation efficiency, defined in the model as the fraction of the total outflow of Pb from plasma that is assigned to the urinary bladder contents, was empirically set to 0.85 to provide the best fit to the PbB measurements during the chelation period. Table 4 (21)(22)(23)(24).…”
Section: Simulated Chelation Therapymentioning
confidence: 99%
“…In the study by Gerhardsson et al conducted [33] 367 0.83 0.056 ± 0.002 in 1988, they were able to measure tibia and calcaneus lead in both active and retired workers. In both groups, there were very extensive records of blood lead measurements, because such monitoring had begun at that lead smelting facility in 1950.…”
Section: Bone Pb and Endogenous Exposurementioning
confidence: 94%
“…The different slope between blood lead on the one hand and tibia lead or calcaneus lead on the other is presumed to reflect the fact that these are different types of bones, with tibia being predominantly cortical and calcaneus being predominantly trabecular. [35] B = 0.17T + 13 Fleming et al [33] B = 0.136T + 13.0 Erkkilä et al [30] B = 0.072C + 4.0 Gerhardsson et al [31] B = 0.062C + 6.9 Fleming et al [33] B = 0.078C + 13.0…”
Section: Bone Pb and Endogenous Exposurementioning
confidence: 97%